Cerebral activity manipulation of low-frequency repetitive transcranial magnetic stimulation in post-stroke patients with cognitive impairment - Yingli, Bi; Zunke, Gong; Wei, Chen; Shiyan, Wang (Frontiers in Neurology, 2022)
Objective: To evaluate the therapeutic effect of low frequency repetitive transcranial magnetic stimulation (rTMS) on post-stroke cognitive impairment (PSCI). Methods: Thirty-six PSCI patients were randomly divided into treatment and control groups of equal size. Both groups were treated with conventional cognitive rehabilitation training. Then, the treatment group was treated with 1 Hz low frequency repetitive transcranial magnetic stimulations, whereas the control group was treated with placebo stimulations. Patients were evaluated via the LOTCA scale assessments and changes in P300 latencies and amplitudes before and after eight weeks of treatment. Results: Before treatment, there were no significant differences between the two groups in LOTCA scores, P300 latencies, and amplitudes (P > 0.05). After treatment, LOTCA scores for both groups improved (P < 0.05), and those of the treatment group were higher than those of the control (P < 0.05). For both groups, P300 latencies were not only shortened but also had greater amplitudes (P < 0.05), and those for the treatment group were significantly shorter and larger than those of the control (P < 0.05). Conclusion: As a therapy, rTMS improved cognitive function in PSCI patients, possibly via regulation of neural electrical activity of the cerebral cortex.